Community participation for rural health: a review of challenges. (3rd December 2014) - Kenny, Amanda; Farmer, Jane; Dickson‐Swift, Virginia; Hyett, Nerida
Abstract: Context: Internationally, community participation is highlighted in health policy reform as good for rural communities. Implicit in this policy is the message that the complexities of the rural environment are too difficult for easy solutions and that community participation will somehow build resilient, self‐determining communities capable of dealing with complex rural access and equity issues and poorer health outcomes. The underpinning proposition is that by giving decision‐making powers to community members, health care will be locally responsive, costs will be contained, and health outcomes will improve. What happens in the practice of enacting community participation in health‐care decision making is less clear. Objective: Despite the growing body of work that documents different levels and models of community participation, significant gaps that outline the practical challenges inherent in rural community participation remain. In this article, we draw on a body of literature to outline the practical considerations in implementing community participation policy in health settings in rural areas. Through a critical review, we aim to stimulate debate, progress ideas and provide a conceptual representation of the somewhat 'messy' nature of rural community participation at a grass‐roots organizational level. Discussion and conclusion: Based on our analysis of the current literature, we provide a summary of challenges and practical strategies that might mitigate some of these challenges. Our review highlights that despite policymakers suggesting that community participation is good for rural communities, policy enactment must move beyond mandated tokenism for there to be a recognition that meaningful participation is neither easy nor linear.